Why Should We Pay More Attention to Skills Deployment? - Karmaeva, Natalia (Journal of Economic Sociology, 2019)
In this book, the issues of skills formation and utilization in the system of formal education and in the labor market are discussed. The recent mainstream concepts of skills are critically analyzed alongside the less known, alternative perspectives. The book addresses several myths related to skills formation and deployment. The first one concerns the relationship between skills and wages; the second is about the demand for “soft” skills in the future economy; the third one addresses the growth of high-skilled jobs; and the fourth one looks at supply-led skills policies. In the handbook, the necessity of a paradigmatic shift from skills formation towards their better utilization is discussed across the fields of education sciences, economics, and political studies. Based on the analysis of recent empirical evidence, the authors elaborate the concepts of social construction of skills, “skills ecosystems,” capabilities and skills, and others. The authors compare institutions and skills policies, including the systems of qualifications, in various countries. Still, most of the empirical illustrations and theoretical concepts presented in the book refer rather to the developed market economies, whereas the analysis of the situation in other countries, in particular, in BRICS, is quite limited. Nevertheless, the handbook is without doubt of high interest to the Russian readership, as it is, probably, the first successful attempt to systematize and critically reassess the existing knowledge in the fields of skills formation and utilization.